Analyzing a clinical case of married couple with combined infertility - A. V. Ledina; G. G. Ketova (Акушерство, гинекология и репродукция, 2022)
Infertility is a disease of the reproductive system characterized by lacked clinical pregnancy after 12 or more months of regular unprotected sex. To diagnose the causes and choose the tactics of infertility treatment, a personalized approach to each patient is required, which is beneficial for both the doctor and the patient. A comprehensive examination of patients is important from the point of pharmacoeconomics and clinical efficiency view. Here, a comprehensive diagnostics of the spouses resulting in birth of a healthy child is discussed.